Role of Photoprotective Systems of Holm-Oak (Quercus ilex) in the Adaptation to Winter Conditions - García-Plazaola, Josá I.; Artetxe, Unai; Duñabeitia, Miren K.; Becerril, Josá M. (Journal of Plant Physiology, 1999)
Holm-oak (Quercus ilex L.) is a Mediterranean evergreen sclerophyllous species adapted to a wide range of environmental conditions and consequently its leaves must be able to withstand variable stresses. Changes in pigment and antioxidant composition were assessed in relation to chilling stress, light environment and leaf aging. Photosynthetic capacity during winter was rwo-fold higher than in spring. However, the photochemical efficiency of PSI! was reduced in sun leaves probably because of an increased rate of thermal energy dissipation related to the superior zeaxanthin concentration. Lutein, neoxanthin, ~-carotene and the xanthophyll cycle pool increased during winter especially in sun leaves, while lutein epoxide and a-carotene decreased markedly. The main antioxidant accumulated during winter was ascorbate, while glutathione and a-tocopherol were not seasonally affected. Catalase increased in spring as a consequence of higher photorespiration rates, while GR and MOHAR activities were higher in sun leaves during winter. The high MOHAR activity indicates an important role for this enzyme in the adaptation to environmental factors associated to winter. The present study demonstrates that holm-oak is able to acclimate to a variety of environmental stress factors by inducing dramatic changes in their photosynthetic characteristics, pigment composition and antioxidant defences.
Keywords: antioxidants; chilling; Mediterranean evergreens; Quercus ilex; sun/shade; xanthophylls

Role of Photoprotective Systems of Holm-Oak (Quercus ilex) in the Adaptation to Winter Conditions (Journal of Plant Physiology, 1999)
Holm-oak (Quercus ilex L.) is a Mediterranean evergreen sclerophyllous species adapted to a wide range of environmental conditions and consequently its leaves must be able to withstand variable stresses. Changes in pigment and antioxidant composition were assessed in relation to chilling stress, light environment and leaf aging. Photosynthetic capacity during winter was rwo-fold higher than in spring. However, the photochemical efficiency of PSI! was reduced in sun leaves probably because of an increased rate of thermal energy dissipation related to the superior zeaxanthin concentration. Lutein, neoxanthin, ~-carotene and the xanthophyll cycle pool increased during winter especially in sun leaves, while lutein epoxide and a-carotene decreased markedly. The main antioxidant accumulated during winter was ascorbate, while glutathione and a-tocopherol were not seasonally affected. Catalase increased in spring as a consequence of higher photorespiration rates, while GR and MOHAR activities were higher in sun leaves during winter. The high MOHAR activity indicates an important role for this enzyme in the adaptation to environmental factors associated to winter. The present study demonstrates that holm-oak is able to acclimate to a variety of environmental stress factors by inducing dramatic changes in their photosynthetic characteristics, pigment composition and antioxidant defences.